2021
DOI: 10.3390/ijerph181910004
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Palliative Care Is Less Utilized in Rare, Fatal Extrahepatic Cholangiocarcinoma: A Ten-Year National Perspective

Abstract: Background—Extrahepatic cholangiocarcinoma (ECC) is a rare, morbid, fatal cancer with distressing symptoms. Maintaining a high quality of life while reducing hospital charges and length of stay (LOS) for the end-of-life period remains a major challenge for the healthcare system. Palliative care utilization has been shown to address these challenges; moreover, its use has increased in recent years among cancer patients. However, the utilization of palliative care in rare cancers, such as ECC, has not yet been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Observed wide differences may partly reflect differences in the study periods since palliative care utilisation has been increasing in recent years (Liu et al, 2019). Increases likely result from several factors, including the growth in the number of hospitals providing palliative care services, the implementation of the Patient Protection and Affordable Care Act (ACA), and the accumulating evidence of palliative care benefits (2019; Liu et al, 2019), such as a reduction in hospital charges (Kelley & Morrison, 2015; Liu et al, 2019; Mojtahedi et al, 2021; Mulvey et al, 2016). Of note, our study found palliative care utilisation sizably reduced hospital charges during a given admission by an average of $12,405.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observed wide differences may partly reflect differences in the study periods since palliative care utilisation has been increasing in recent years (Liu et al, 2019). Increases likely result from several factors, including the growth in the number of hospitals providing palliative care services, the implementation of the Patient Protection and Affordable Care Act (ACA), and the accumulating evidence of palliative care benefits (2019; Liu et al, 2019), such as a reduction in hospital charges (Kelley & Morrison, 2015; Liu et al, 2019; Mojtahedi et al, 2021; Mulvey et al, 2016). Of note, our study found palliative care utilisation sizably reduced hospital charges during a given admission by an average of $12,405.…”
Section: Discussionmentioning
confidence: 99%
“…Although palliative care is ideally provided throughout serious illnesses alongside curative therapies, most patients referred to inpatient palliative care services have been shown to be at the end of life (Liu et al, 2019; Mojtahedi et al, 2021). We found that palliative care utilisation was much higher during hospitalizations ending in death compared to those with alive discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The palliative care team is multidisciplinary and consists of physicians, nurses, social workers, and other specialists to cover a range of conditions from pain to emotional/ financial challenges of patients, their families, or caregivers. 1,3 In addition, the palliative care team discusses with patients advance care planning, a process that enables patients to express their values and preferences for future care. 4 Palliative care can be offered in different settings, such as hospitals, hospice facilities, out-patient clinics, nursing homes, and home.…”
Section: Introductionmentioning
confidence: 99%